2018
DOI: 10.1124/dmd.118.081794
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Assessment of Transporter-Mediated Drug–Drug Interactions Using a Probe Drug Cocktail in Cynomolgus Monkey

Abstract: We aim to establish an in vivo preclinical model to enable simultaneous assessment of inhibition potential of an investigational drug on clinically relevant drug transporters, organic anion-transporting polypeptide (OATP)1B, breast cancer resistance protein (BCRP), P-glycoprotein (P-gp), and organic anion transporter (OAT)3. Pharmacokinetics of substrate cocktail consisting of pitavastatin (OATP1B substrate), rosuvastatin (OATP1B/BCRP/OAT3), sulfasalazine (BCRP), and talinolol (P-gp) were obtained in cynomolgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 63 publications
(111 reference statements)
8
37
0
Order By: Relevance
“…Hence, another OAT1/3 probe may be more reliable ( Figure b ). Recently, a substrate cocktail consisting of pitavastatin (OATP1B), rosuvastatin (OATP1B/BCRP/OAT3), sulfasalazine (BCRP), and talinolol (P‐gp) was evaluated in cynomolgus monkey …”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Hence, another OAT1/3 probe may be more reliable ( Figure b ). Recently, a substrate cocktail consisting of pitavastatin (OATP1B), rosuvastatin (OATP1B/BCRP/OAT3), sulfasalazine (BCRP), and talinolol (P‐gp) was evaluated in cynomolgus monkey …”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Clinical DDI studies with cocktail substrates reduce the number of clinical trials, speed up drug development processes and enable better ethical compliance (Trueck et al, ). Similar cocktail approaches have been reported in human with micro‐dosing and in cynomolgus monkeys for both major CYPs and transporters (Kosa et al, ; Prueksaritanont et al, ). For transporter‐mediated DDI, cynomolgus monkey has been found to be a good model for prediction of OATP1B, BCRP, P‐gp, and OAT3 mediated DDI in humans (Kosa et al, ).…”
Section: Transporter‐mediated Ddimentioning
confidence: 52%
“…Animal models typically cannot reliably predict human DDIs, with the exception of a few reports on transporter DDIs. It has been shown that cynomolgus monkey may be a viable model to predict the activities and DDIs of major drug transporters in humans such as OATP1Bs, OAT3, P‐gp, and BCRP (Kosa et al, ). Both static or dynamic models are available for human DDI prediction.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro work suggests that probenecid has lower inhibitory activity vs resveratrol sulfate formation compared with the glucuronide conjugation pathway . Also, probenecid minimally inhibits transport mediated by P‐gp …”
Section: Discussionmentioning
confidence: 99%
“…[70] Also, probenecid minimally inhibits transport mediated by P-gp. [71][72][73] The observed in vitro inhibition of glucuronidation by probenecid translates to clinical DDIs, in which coadministration of usual therapeutic doses of probenecid causes reduced clearance and increased plasma concentrations of a number of substrate drugs cleared mainly by glucuronide conjugation. Examples of affected substrates include paracetamol (acetaminophen), lorazepam, oxazepam, temazepam, diflunisal, zomepirac, zidovudine, and naproxen.…”
Section: Discussionmentioning
confidence: 99%